A potential role for T-type calcium channels in homocysteinemia-induced peripheral neuropathy. Issue 12 (December 2019) - Gaifullina, Aisylu S.; Lazniewska, Joanna; Gerasimova, Elena V.; Burkhanova, Gulshat F.; Rzhepetskyy, Yuriy; Tomin, Andriy; Rivas-Ramirez, Paula; Huang, Junting; Cmarko, Leos; Zamponi, Gerald W.; Sitdikova, Guzel F.; Weiss, Norbert
Abstract : Abstract: Homocysteinemia is a metabolic condition characterized by abnormally high level of homocysteine in the blood and is considered to be a risk factor for peripheral neuropathy. However, the cellular mechanisms underlying toxic effects of homocysteine on the processing of peripheral nociception have not yet been investigated comprehensively. Here, using a rodent model of experimental homocysteinemia, we report the causal association between homocysteine and the development of mechanical allodynia. Homocysteinemia-induced mechanical allodynia was reversed on pharmacological inhibition of T-type calcium channels. In addition, our in vitro studies indicate that homocysteine enhances recombinant T-type calcium currents by promoting the recycling of Cav 3.2 channels back to the plasma membrane through a protein kinase C–dependent signaling pathway that requires the direct phosphorylation of Cav 3.2 at specific loci. Altogether, these results reveal an unrecognized signaling pathway that modulates the expression of T-type calcium channels, and may potentially contribute to the development of peripheral neuropathy associated with homocysteinemia. Abstract : Supplemental Digital Content is Available in the Text.Homocysteine modulates T-type calcium channel expression through a protein kinase C–dependent signaling pathway and possibly contributes to homocysteinemia-induced mechanical allodynia.